HUBUNGAN ANTARA POLA MAKAN DENGAN DERAJAT KEPARAHAN DISMINORE PADA MAHASISWA UNIVERSITAS ISLAM NEGERI SUMATRA UTARA - Shofiyyah Adilah; Putra Apriadi Siregar (Jurnal Kesehatan, 2023)
Menstrual disturbances that are often felt by young women are dysmenorrhea or menstrual pain. Dysmenorrhea is pain during menstruation, usually in the form of cramps and is concentrated in the lower abdomen. Dysmenorrhea is often experienced by women of reproductive age, which is around 45% to 93% and the highest incidence of dysmenorrhea is experienced by adolescents. The purpose of this study was to determine the relationship between diet and the severity of dysmenorrhea in students at the Faculty of Public Health, Uinsu. This research method is quantitative, where the independent variable, namely diet and the dependent variable, namely the severity of dysmenorrhea, will be collected at the same time. This research was conducted through the stage of distributing questionnaires using the G-form to UINSU public health faculty students. There is a relationship between the severity of dysmenorrhea and a diet based on carbohydrate intake. There is also no relationship between dysmenorrhea and a diet based on protein and fat intake.